The nature of fire phenomena during the 1927 Crimean earthquakes - В.П. Коболєв; В.В. Янко (Геофизический журнал, 2025)
During the Crimean earthquakes of 1927, incomprehensible natural phenomena were observed in the Black Sea — flashes of fire above the water (henceforth referred to as the fire phenomena). It was originally believed that these phenomena were associated with ignition of methane, which had escaped from the seabed due to tectonic disturbances formed during seismic movements.